Flavonoids and lignans from Virola surinamensis twigs and their in vitro activity against Trypanosoma cruzi - Lopes, N. P.; Chicaro, P.; Kato, M. J.; Albuquerque, S.; Yoshida, M. (Georg Thieme Verlag, 1998)
Dichloromethane extracts from twigs of Virola surinamensis (Myristicaceae) showed in vitro trypanosomicidal activity against trypomastigote form of Trypanosoma cruzi. The extract, fractionated by preparative circular chromatography and preparative high-performance liquid chromatography yielded two steroids, two lignans, five flavonoids, and one polyketide. Among the isolated compounds, the lignans presented the highest trypanosomicidal activity.